Preparation of PDMS permeation membrane by emulsion dilution method and its separation performance for aromatics - Meiluan Wang; Fang Ni; Ziling Teng; Zixuan Ge; Qi Liu; Benwei Zhu; Huiyun Liao; Zhong Yao (AIP Advances)
Natural aroma compounds are a kind of important food additive. Taking bis(2-ethylhexyl) sodium sulfosuccinate (AOT) as the surfactant, water-in-n-heptane emulsions were prepared. Then, the emulsions were adopted as the diluter to prepare polydimethylsiloxane (PDMS) pervaporation membranes using the emulsion templating method (ePDMS), of which the separation layer was controlled by the template action of emulsion drops. The ePDMS membranes were utilized to separate aroma compounds. Field-emission scanning electron microscope (FESEM) analysis revealed that the surface of the ePDMS membrane remained smooth, and white light interferometry confirmed the membrane’s surface smoothness. FESEM cross-sectional analysis exposed the voids left by the evaporation of the emulsion, rendering the separation layer of the ePDMS membrane more porous. Water contact angle measurements demonstrated the hydrophobicity of the ePDMS membrane, which is advantageous for the pervaporation of aromatic compounds. Fourier transform infrared spectrometry analysis confirmed the evaporation and separation of the emulsion, retaining the original chemical properties of the PDMS membrane. In an ethanol–water system, the permeation flux of ethanol in ePDMS membranes prepared with 1 emulsion (Vwater:Vn-heptane = 1:9; mass concentration of AOT of 1.0 mg/ml) is 90.6% higher than that in PDMS membranes, while the separation factor does not change obviously. The separation performance of ePDMS membranes for linalool in water was further studied. Results show that the permeation flux and separation factor of linalool in ePDMS composite membranes at 50 °C are 786 g m−2 h−1 and 17.69, which separately increase by 84.7% and 27.1% compared with those in PDMS membranes. This indicates that adding ethanol exerts a significant synergistic effect on the separation of linalool.